Financial contracts and contingent control rights - Jukka Vauhkonen (Bank of Finland, 2003)
According to empirical studies of venture capital finance, the division of control rights between entrepreneur and venture capitalists is often contingent on certain measures of firm performance.If the indicator of the company's performance (eg earnings before taxes and interest) is low, the venture capital firm obtains full control of the company.If company performance improves, the entrepreneur retains or obtains more control rights. If company performance is very good, the venture capitalist relinquishes most of his control rights.In this article, we extend the incomplete contracting model of Aghion and Bolton to construct a theoretical model that is consistent with these empirical findings.
URN:NBN:fi:bof-20140807299
Keywords: G32; 330; incomplete contracts; financial contracting; contingent contracts; control rights; joint ownership